Research and Development of Mobile Intelligent Management Systemfor Regional Small Reservoir Group Based on GIS - JIN Xi; LIN Ling; YU Yangfeng; MA Fuheng (Renmin Zhujiang)
In China, there are many small reservoirs located in remote areas, which brings a lot ofinconvenience for reservoir safety monitoring and management. In order to improve the managementlevel of small reservoir group, this paper firstly collates and summarizes the monitoring andmanagement characteristics of small reservoir group, and then constructs a mobile intelligentmanagement system framework for regional small reservoir group based on GIS and analyzes, the keytechnologies in the constructing process, finally taking the small reservoir group in WenlingCity, Zhejiang Province as an example, develops a mobile intelligent management system of thesmall reservoir group. Through this system, the engineering information query, video monitoringand real-time monitoring and analysis of monitoring data can all be realized, and the real-timedynamic situation of each reservoir can be mastered in a timely and accurate way, to providescientific basis for improving the management level and decision-making of small reservoirs.